ANGGARAN BIAYA PRODUKSI MINYAK GORENG DENGAN PENDEKATAN BIAYA VARIABEL PADA TEACHING FACTORY POLITEKNIK NEGERI LHOKSEUMAWE - Ali Imran; Teuku Mustaqim; Ismed Wijaya; Zuarni Zuarni; Sutoyo Sutoyo (Ekonis: Jurnal Ekonomi dan Bisnis, 2020)
This study aims to design a production cost budget at the Teaching Factory for cooking oil, chemical engineering department of the Lhokseumawe State Polytechnic. The research method used is descriptive qualitative, where the researcher will explore production data on the object of research and then compile the data into a production cost budget based on previous research studies and based on existing literature. This research is interesting because the cooking oil installation in the laboratory is different from the general factory, this is because the installation assets are included in BMN so that they cannot be included separately in the calculation of the production cost budget if the installation is carried out economically. This research can provide an ideal production cost budget calculation model in a laboratory at a state university or polytechnic.Keywords: Design, Budget, Cost, Production, Laboratory